Про існування неперервних розв’язків систем різницевих рівнянь - Бецко, І.В. (Нелінійні коливання, 2016)
Установлены условия существования непрерывных ограниченных решений систем разностных уравнений с линейно преобразованным аргументом и разработан метод их построения. We find conditions for existence of continuous bounded solutions to a sistem of difference equations with linearly transformed argument, and develop a method to construct such solutions.